Correlação entre processos de fabricação convencional e por manufatura aditiva com as propriedades do aço inoxidável 316L - Souza, Lídia Beatriz Oliveira de (2022)
Unlike the most well-known manufacturing processes, which use subtraction to produce a component, additive manufacturing is based on the progressive addition of thin layers of material to manufacture a part. The possibility of producing highly complex or customized parts, in fewer steps and saving material, has been one of the attractions of this manufacturing method. However, there are still challenges for the application of this process, since different regions of the material being produced undergo different thermal cycles, which can cause microstructural changes and changes in the mechanical properties of the alloy. Thus, this work aimed to characterize 316L stainless steel manufactured by two additive manufacturing processes with different natures, WAAM and SLM. Tube samples manufactured by these processes were subjected to chemical composition testing via mass discharge spectrometry. Microstructural analysis by optical microscopy and scanning electron microscopy. And characterization of mechanical behavior through microhardness measurements and tensile and bending test. For comparison purposes, the same analyzes were performed with a tube of the same alloy in the annealed condition. It could be observed that the component produced by WAAM presented a ferritic-austenitic microstructure, with different ferrite morphologies, unlike the austenitic structure of the conventional material and the one manufactured by SLM. The two additive manufacturing processes produced a microstructure with a smaller grain size than the annealed material, resulting in an increase in the microhardness and in the creep limit of the material, as well as lower ductility. The SLM was the technique that presented the smallest grain size, the highest microhardness, and the highest yield strength. The different microstructures of the WAAM process caused a great dispersion of the microhardness values that contributed to a greater anisotropy of the material, which resulted in the component with the lowest ductility among those analyzed